The perspectives of STEM faculty toward undergraduate mentorship - A case study - Pamela Martínez Oquendo; Morgan D. Vogel (International Journal of Evidence Based Coaching and Mentoring)
A plethora of research captures undergraduate students' perceptions of faculty mentorship in science, technology, engineering, and mathematics (STEM). However, more research is necessary to capture the perceptions of STEM faculty about the mentor-mentee relationship. This study aimed to capture the perspectives of STEM faculty toward undergraduate mentorship. We used a case study methodology with six STEM faculty members to answer our research questions. We used the theoretical framework proposed by Crisp and Cruz (2009). We found that the STEM faculty-student mentoring relationship involves strong psychological support.